Factors That Influence Intention to Adopt Mobile Shopping in Marketplace - Dudi Anandya; Geraldus Grady Gavindra; Indarini Indarini (Management Institute Faculty of Economics Universitas Andalas, 2023)
The economic industry has been affected by digitalization which has grown rapidly. This growth opens up new opportunities in industrial processes including in transaction and shopping methods. One of the growing transactions is mobile shopping. This study aims to determine the factors that can influence the intention to adopt mobile shopping on the Tokopedia application with a scope in Surabaya. The intention to adopt mobile shopping variable examined in this research is influenced by: attitude toward mobile shopping, subjective norm, self-efficacy, trust, perceived risk, and perceived cost. This study used data sources from online questionnaires and had 273 data from respondents who met the criteria. This respondent data was processed through SPSS 24 and AMOS Graphics 22 software using Structural Equation Modeling (SEM) techniques. The results of data processing show that attitude toward mobile shopping, self-efficacy, trust, perceived cost are factors that influence intention to adopt mobile shopping on the Tokopedia application in Surabaya.